Pendidikan Sosial “Anti Bullying” di SDN Gondek Jombang oleh Peserta KKN-T UPN “Veteran” Jawa Timur - Herwinda Anggun Permata; Narisyah Evita; Roziana Febrianita (Jurnal Kabar Masyarakat, 2024)
Bullying has long been a part of school life and is an issue that has a negative impact on children's growth and development. This research aims to increase awareness about bullying through outreach carried out at SD Negeri Gondek, Jombang, East Java. This socialization was carried out in the context of the Thematic Real Work Lecture (KKN-T) program to provide education to class IV and V students about the dangers of bullying and the importance of creating a safe school environment. The results of the socialization show that students' understanding of bullying has increased significantly, whereas previously most students were not aware of the impact of this action. This program was successful in changing students' perceptions and encouraging their active participation in preventing bullying at school. The success of this initiative highlights the importance of collaboration between schools, teachers, parents and students in ongoing efforts to create inclusive and safe environments. Regular evaluation and further development of supporting programs is highly recommended to ensure the sustainability and effectiveness of this program.